Health Inequality in Eight Adverse Outcomes Over a 25-Year Period in a Multi-Ethnic Population in New Zealand Population with Impaired Glucose Tolerance and/or Impaired Fasting Glucose: An Age-Period-Cohort Analysis - Wang Z; Yu D; Osuagwu UL; Pickering K; Baker J; Cutfield R; Cai Y; Orr-Walker BJ; Sundborn G; Zhao Z; Simmons D (Clinical Epidemiology, 2023)
Zheng Wang,1,* Dahai Yu,1,2,* Uchechukwu Levi Osuagwu,3,4 Karen Pickering,5 John Baker,5,6 Richard Cutfield,5,7 Yamei Cai,1 Brandon J Orr-Walker,5,6 Gerhard Sundborn,8 Zhanzheng Zhao,1 David Simmons1,4 1Department of Nephrology, The First Affiliated Hospital, Zhengzhou University, Zhengzhou, 450052, People’s Republic of China; 2Primary Care Centre Versus Arthritis, School of Medicine, Keele University, Keele, ST5 5BG, UK; 3Translational Health Research Institute (THRI), Western Sydney University, Campbelltown, Sydney NSW, 2560, Australia; 4School of Medicine, Western Sydney University, Campbelltown, Sydney NSW, 2751, Australia; 5Diabetes Foundation Aotearoa, Otara, New Zealand; 6Department of Diabetes and Endocrinology, Counties Manukau Health, Auckland, New Zealand; 7Department of Diabetes and Endocrinology, Waitemata District Health Board, Auckland, New Zealand; 8Section of Pacific Health, The University of Auckland, Auckland, New Zealand*These authors contributed equally to this workCorrespondence: David Simmons; Zhanzheng Zhao, Department of Nephrology, The First Affiliated Hospital Zhengzhou University, Zhengzhou, 450052, People’s Republic of China, Tel +6124620 3899 ; +86 13938525666, Fax +6124620 3890 ; +863716698 8753, Email Da.Simmons@westernsydney.edu.au; zhanzhengzhao@zzu.edu.cnPurpose: We aimed to examine socioeconomic inequality (SI) in cause-specific outcomes among adults with impaired glucose tolerance (IGT) and/or Impaired fasting glucose (IFG) in New Zealand (NZ) over 25 years.Patients and Methods: A population-based open cohort was derived from Diabetes Care Support Service in NZ with national databases linkage. Patients aged ≥ 18 years with IGT and/or IFG were enrolled between 01/01/1994 and 31/07/2018 and followed up until death or 31/12/2018. Incident outcomes (all-cause, premature, cardiovascular, and cancer death; cardiovascular, myocardial infarction, stroke, heart failure, and end-stage kidney disease hospitalization) by demographic, anthropometric, socioeconomic status, clinical measurements, enrol-time-periods, and IGT/IFG were evaluated. Adjusted incidence rate ratios, absolute risk difference, and SI measurements (slope and relative index of inequality) were estimated using Age-Period-Cohort models.Results: 29,894 patients (58.5 (SD 14.3) years mean age; 52.2% female) were enrolled with 5.6 (IQR: 4.4– 7.4) years of median follow-up. Mortality rates decreased, whereas hospitalization (except myocardial infarction) rates increased. SI was significant for each outcome. Higher mortality and hospitalization rates and worsened SI were common in men, older, the most deprived, and Māori patients, as well as patients with obesity, current smoking, with both IFG and IGT, and greater metabolic derangement (higher systolic blood pressure, lipids, and HbA1c, and lower level of mean arterial pressure).Conclusion: Enhanced management strategies are necessary for people with IGT and/or IFG to address persisting SI, especially for men, older people, current smokers, NZ European and Māori patients, patients with obesity, or with any abnormal metabolic measurements.Keywords: impaired glucose tolerance, impaired fasting glucose, New Zealand, Māori, ethnic disparity, socioeconomic inequality, mortality, cardiovascular diseases, heart failure, cancer, end-stage renal disease